The increasing significance of digital equity in higher education: An introduction to the Digital Equity Special Issue - Willems, Julie; Farley, Helen; Campbell, Chris (Australasian Journal of Educational Technology, 2019)
Digital equity is a complex and multifaceted concept. It includes not only access to hardware, software, and connectivity to the Internet but also meaningful, high-quality, and culturally relevant content in local languages, and the ability to create, share, and exchange knowledge. Participatory citizenship in the digital era involves the right to access and participate in higher education. Indeed, it is a key civil rights issue of the modern world. This editorial provides the context in which the articles in this special issue are located.